Wujud Kepedulian Mahasiswa melalui Kegiatan Pembagian Sembako dan Pakaian Layak Pakai - Fakhriyyah, Jihan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Poverty and limited access to basic necessities such as food and clean clothing remain crucial issues that undermine the quality of life and dignity of the community. In response to this urgency, this Community Service (PkM) activity was implemented through the distribution of basic food supplies and suitable clothing. This program aims to provide direct assistance while simultaneously developing the character of students who are empathetic, responsible, and possess a high level of social sensitivity. The method employed in this activity is Participatory Action Research (PAR), which emphasizes active participation between students and the community as the primary subjects. The implementation results indicate that the PAR-based PkM approach is effective in alleviating the economic burden on recipients while fostering collective awareness of the importance of social awareness. In addition to providing material benefits, this activity has successfully served as an effective character-building medium for students and the surrounding community. This initiative can serve as inspiration and a reference for other community service programs in the future to improve welfare and social awareness.